Are you ready for the global change? Multicultural personality and readiness for organizational change - Caliskan, Sibel; Isik, Idil (Emerald Group Publishing Ltd, 2016)
Purpose - The purpose of this paper is to investigate employee readiness for their organizations' global change and the predictive effect of their personality and perception of change. Design/methodology/approach - Participants were from work groups that are known to have various levels of contribution to the globalization process in a retail company. Following focus group study, surveys of multicultural personality (MP), organizational change (OC) perception, and individual readiness for global change were conducted. Findings - Results showed that the participants from the work groups with higher involvement in global work evaluated themselves more in terms of MP characteristics, with a more positive perception of OC process and climate, and more readiness for change. There was no effect of MP on OC perception or readiness for change. Perceived OC partially mediated the relationship between the perceived global content of the job and individual readiness for change. Research limitations/implications - The sample is relatively small which limits the external validity of the findings. Practical implications - Results revealed the importance of recruiting the right employees and corporate communication during the globalization process among all work groups. Originality/value - This study is one of the first that integrates OC in the process of globalization with employees' MP. Further, it elaborates on how the perception of and readiness for OC differs across diverse work units throughout the globalization process.
Keywords: Globalization; Organizational Change; Readiness For Change; Multicultural Personality; Work Groups; Questionnaire; Validity